Head Start Teachers' Professional Development, Well‐being, Attitudes, and Practices: Understanding Changes Over Time and Predictive Associations. Issue 3 (22nd May 2019) - Harding, Jessica F.; Connors, Maia C.; Krauss, Allison Friedman; Aikens, Nikki; Malone, Lizabeth; Tarullo, Louisa
Highlights: The professional development supports available to teachers predicted higher job satisfaction and more math activities. Early care and education teachers' curriculum support was related to more frequent math activities. Early care and education teachers' mentoring support predicted more developmentally appropriate attitudes. Many types of professional development were not associated with teachers' well‐being, attitudes, or practices. Teachers' professional development, well‐being, attitudes, and practices did not increase across cohorts. Abstract: Early care and education (ECE) teachers shape children's daily experiences in many ways. Specifically, teachers' well‐being, attitudes about child development, and teaching practices are central influences on children's learning. One crucial way ECE programs support teachers to enhance children's learning environments is through the provision of professional development (PD), but little research has examined the PD provided by ECE programs in the absence of focused initiatives to support teachers. In this descriptive study, we use data from a nationally representative study of Head Start teachers ( N  = 484) to explore whether teachers' job satisfaction, depression, developmentally appropriate attitudes, and frequency of engagement in math and literacy activities are associated with the number of (a) overall PD supports available to teachers, (b) curriculum supports received by teachers, and (c) mentoring supports received by teachers. Many of the associations between teachers' outcomes and overall PD supports, curriculum supports, and mentoring supports were not statistically significant, perhaps because the PD variables do not measure the quality or content of the PD provided. However, those PD supports that were significantly associated with outcomes were associated with specific teacher outcomes in ways consistent with theory, although associations were relatively weak. To contextualize these findings, we describe how PD supports and teachers' outcomes have changed over nearly a decade that encompasses some key Head Start policy changes. This research contributes to our understanding of scalable ways to prepare and support teachers of some of the nation's most vulnerable children.